Nexus of Inter-organizational Trust, Principled Negotiation, and Joint Action for Improved Cost Performance: Survey of Chinese Megaprojects - Li, Q.; Yin, Z.; Chong, Heap Yih; Shi, Q. (ASCE, 2018)
Drawing on the theory of relational governance, this study determined the nexus of interorganizational trust, principled negotiation, and joint action in cost performance. To this end, five hypotheses were formulated based on established management theories or principles of organizational studies. The study used partial least squares structural equation modeling to analyze the 248 valid questionnaires collected from the analyzed organizations involved in megaprojects. The results show that interorganizational trust has direct and indirect positive effects on improving cost performance. Principled negotiation and joint action can serve as multiple mediating roles between interorganizational trust and cost performance. Contractual governance also has different moderation effects on principled negotiation and joint action toward cost performance. In conclusion, this study contributes to the knowledge on interorganizational trust and its mediating effects on cost performance from the perspective of megaprojects. The results are generalizable to other projects with complicated organizational and working relationships.